Crystal structures of three co-crystals of 4,4′-bipyridyl with 4-alkoxybenzoic acids: 4-ethoxybenzoic acid–4,4′-bipyridyl (2/1), 4-n-propoxybenzoic acid–4,4′-bipyridyl (2/1) and 4-n-butoxybenzoic acid–4,4′-bipyridyl (2/1) - Yohei Tabuchi (Acta Crystallographica Section E: Crystallographic Communications, 2015)
The crystal structures of three hydrogen-bonded co-crystals of 4-alkoxybenzoic acid–4,4′-bipyridyl (2/1), namely, 2C9H10O3·C10H8N2, (I), 2C10H12O3·C10H8N2, (II) and 2C11H14O3·C10H8N2, (III), have been determined at 93 K. Although the structure of (I) has been determined in the space group P21 with Z = 4 [Lai et al. (2008). J. Struct. Chem. 49, 1137–1140], the present study shows that the space group is P21/n with Z = 4. In each crystal, the components are linked by O—H...N hydrogen bonds, forming a linear hydrogen-bonded 2:1 unit of the acid and the base. The 2:1 unit of (I) adopts nearly pseudo-C2 symmetry, viz. twofold rotation around an axis passing through the mid-point of the central C—C bond of 4,4′-bipyridyl, while the units of (II) and (III), except for the terminal alkyl chains, have pseudo-inversion symmetry. The 2:1 units of (I), (II) and (III) are linked via C—H...O hydrogen bonds, forming sheet, double-tape and tape structures, respectively.